MENANAMKAN PROGRAM GERAKAN MASYARAKAT HIDUP SEHAT DI YAYASAN INI MEDIA KITA - Dwianggoro, Prihadi; Alfiah, Siti; Janudin, Janudin; Anhary, Agus Sulaiman; Rahman, Fakung (LPPM Universitas Pamulang, 2020)
The program of community service activities is one of the tasks carried out by lecturers in carrying out the Tri Darma Perguruan Tinggi. The partner in this program is Media Kita Foundation. The main problem faced by partners is the lack of awareness in maintaining the cleanliness of the environment around the school. In this case, especially in the education environment, cleanliness is an inseparable part of the education program itself. A clean environment will certainly give students comfort in learning and of course student health will also be maintained. For this reason, it is necessary to provide counseling on the procedures for a healthy lifestyle where the ultimate goal is to create an awareness that the importance of a healthy lifestyle is consistently applied. This of course requires the involvement of all parties both students, teachers, the surrounding community. In implementing a healthy lifestyle or better known as the healthy living community movement it is expected that health is more maintained, student activities are more productive, the environment is clean and of course will be spared from various unwanted diseases.